Lack of effect of oral Mg-supplementation on Mg in serum, blood cells, and calf muscle - Weller, Ellen; Bachert, Peter; Meinck, Hans-Michael; Friedmann-Bette, Birgit; Bärtsch, Peter; Mairbäurl, Heimo (Medicine and science in sports and exercise, 1998)
Med. Sci. Sports Exerc., Vol. 30, No. 11, pp. 1584-1591, 1998. Magnesium (Mg) is important for regulating ion transport and cellular metabolism in all body tissues. In skeletal muscle Mg is involved in the neuromuscular activity, excitation, and muscle contraction. Mg deficiency can cause muscle weakness and muscle cramps. Less than 1% of total body Mg is found in serum, yet the serum Mg concentration is used to assess the body's Mg status. - Purpose: - The purpose of this study was to determine whether an oral Mg supplementation (500 mg Mg-oxide·d−1 for 3 wk) affects exercise performance, clinical symptoms, and the Mg concentration in various body compartments in athletes with low-normal serum Mg levels (N = 10 in each group). - Methods: - In a double-blind, placebo-controlled study, correlation analysis between the Mg concentration in serum, blood cells, and skeletal muscle was performed to establish a measure for muscle cell Mg. - Results: - The data indicate that a 3-wk Mg supplementation did not affect exercise performance, neuromuscular activity, or muscle related symptoms. Also, the supplementation did not increase the Mg concentration in serum or any cellular compartment studied. However, in the placebo group the renal Mg clearance decreased, whereas it increased in the subjects receiving Mg supplementation. Correlation analysis revealed that serum Mg only correlated with red cell Mg and that only leukocyte Mg correlated with the nuclear magnetic resonance (NMR)-measured muscle cell Mg concentration. - Conclusions: - These results indicate that Mg supplementation in athletes with low-normal serum Mg did not improve performance and failed to increase the body's Mg stores. Serum Mg appears to be a poor indicator for Mg in skeletal muscle or most other cellular compartments, but the concentration of Mg in mononuclear leukocytes might be used as an indicator of skeletal muscle Mg when NMR is not available.
Gesehen am 25.01.2024